A symposium on increasing employment in Ireland - Kennedy, Kieran A. (Statistical and Social Inquiry Society of Ireland, 1976)
The current recession has focussed widespread attention on the employment problem. The present difficulties are evidenced by the very high rate of unemployment, the falling level of employment in manufacturing, and the curtailment of many of the normal job opportunities for school-leavers. In this paper, however, I wish to draw attention to the longer-term employment position, which is compounding the short-term difficulties arising from world depression, and which, if allowed to persist, could entail a far more serious crisis than even the present difficulties.
Read before the Society, 20 November 1975
Keywords: Employment in Ireland; Unemployment in Ireland; Economic development; 314.15